1977
DOI: 10.1016/s0006-3495(77)85543-4
|View full text |Cite
|
Sign up to set email alerts
|

Human red cell hemolysis rates in the subsecond to seconds range. An analysis

Abstract: Hypoosmotic shock kinetics of the normal human red cell (25 degrees C) were investigated by means of a rapid kinetics apparatus, with a resolving time of about 50 ms. The results are compared with some current models for hemolysis. The fast hemolysis plots are not true symmetric sigmoids, in contrast to results from less stressful conditions, nor can they be simply fitted to an "all or none" process. In the most severe conditions, mixing with neat water, the velocities with which red cells start to hemolyze de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 2 publications
4
8
1
Order By: Relevance
“…-~ 8o: It is well known that the haemolysis of the erythrocytes has a typical sigmoidal shape with increasing the NaC1 concentration in the external medium of the cells [1,2]. Our data are in accord with the data presented so far in the literature, the gamma irradiated erythrocytes as well as the unirradiated erythrocytes exhibited a similar typical sigmoidal shape with the increasing NaC1 concentration in the external medium of the cells.…”
Section: Results and Conclusionsupporting
confidence: 90%
“…-~ 8o: It is well known that the haemolysis of the erythrocytes has a typical sigmoidal shape with increasing the NaC1 concentration in the external medium of the cells [1,2]. Our data are in accord with the data presented so far in the literature, the gamma irradiated erythrocytes as well as the unirradiated erythrocytes exhibited a similar typical sigmoidal shape with the increasing NaC1 concentration in the external medium of the cells.…”
Section: Results and Conclusionsupporting
confidence: 90%
“…The two-phase release of hemoglobin described here for a transient osmotic pulse with PBS diluent has also been described for hypotonic lysis by Anderson and Lovrien (1977). In the first phase, the shortest time to initial lysis, obtained with lysis by water, was 0.6 sec.…”
Section: Discussionmentioning
confidence: 77%
“…The abundance of unsaturated fatty acids (Raz and Livne 1973;Shand and Noble 1981;Vajreswari et al 1983) was shown to be related to a greater extent of membrane expansion when cells are exposed to hypotonic solutions. This increase in membrane surface allows an increase in cellular critical volume which is positively correlated with the osmotic resistance (Anderson and Lovrien 1977) when the resulting hemolysis is studied as a function of salt concentration.…”
Section: Discussionmentioning
confidence: 99%